A soft-bodied lophophorate from the Silurian of England. - Sutton, MD; Briggs, D; Siveter, D; Siveter, D (2011)
Soft-bodied taxa comprise an important component of the extant lophophorate fauna, but convincing fossils of soft-bodied lophophorates are extremely rare. A small fossil lophophorate, attached to a brachiopod dorsal valve, is described from the Silurian (Wenlock Series) Herefordshire Lagerstätte of England. This unmineralized organism was bilaterally symmetrical and comprised a subconical body attached basally to the host and partially enclosed by a broad 'hood'; the body bore a small, coiled lophophore. Where the hood attached laterally, there is a series of transverse ridges and furrows. The affinities of this organism probably lie with Brachiopoda; the hood is interpreted as the homologue of a dorsal valve/mantle lobe, and the attachment as the homologue of the ventral valve and/or pedicle. The ridges are arranged in a manner that suggests constructional serial repetition, indicating that they are unlikely to represent mantle canals. Extant brachiopods are not serially structured, but morphological and molecular evidence suggests that their ancestors were. The new organism may belong to the brachiopod stem group, and might also represent a significant element of the Palaeozoic lophophorate fauna.